2019
DOI: 10.3847/1538-4357/ab04af
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Study of Equatorial Coronal-hole Jets

Abstract: Jets (transient/collimated plasma ejections) occur frequently throughout the solar corona and contribute mass/energy to the corona and solar wind. By combining numerical simulations and high-resolution observations, we have made substantial progress recently on determining the energy buildup and release processes in these jets. Here we describe a study of 27 equatorial coronal-hole jets using Solar Dynamics Observatory/AIA and HMI observations on 2013 June 27-28 and 2014 January 8-10. Out of 27 jets, 18 (67%) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 39 publications
12
75
0
Order By: Relevance
“…The properties of the blobs (size, temperature, etc.) were similar to those reported for the plasma blobs in previous AIA observations of flare current sheets (Takasao et al 2012;Kumar & Cho 2013;Kumar et al 2018Kumar et al , 2019. These jet observations also agree with results of the highest-resolution MHD simulations of breakout jets and CMEs, which consistently find that multiple plasmoids form in the breakout and flare current sheets (Karpen et al 2012;Guo et al 2013;Lynch & Edmondson 2013;Lynch et al 2016;Guidoni et al 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The properties of the blobs (size, temperature, etc.) were similar to those reported for the plasma blobs in previous AIA observations of flare current sheets (Takasao et al 2012;Kumar & Cho 2013;Kumar et al 2018Kumar et al , 2019. These jet observations also agree with results of the highest-resolution MHD simulations of breakout jets and CMEs, which consistently find that multiple plasmoids form in the breakout and flare current sheets (Karpen et al 2012;Guo et al 2013;Lynch & Edmondson 2013;Lynch et al 2016;Guidoni et al 2016).…”
Section: Discussionsupporting
confidence: 91%
“…No flare arcade was detected, however, which indicates minimal or no flare reconnection below the filament and thus no flux-rope formation along the PIL. We also interpret the brief appearance of bright spots at the base of the fan, far from the site where flare ribbons would occur, as evidence for particle acceleration on selected field lines comprising the fan surface (Sterling & Moore 2001;Kumar et al 2018). Finally, the bidirectional flows and plasma blobs (plasmoids) coming from the vicinity of the fan-spine intersection are unmistakable signs of magnetic reconnection.…”
Section: Discussionmentioning
confidence: 91%
“…Shen et al [63,69] studied two blowout jets and found that the erupting mini-filaments directly form the cool component of coronal jets (figure 2). Recently, more and more observational studies have confirmed that blowout jets are driven by mini-filament eruptions or filament channels [73][74][75][76][77][78][79][80][81][82][83][84]97,98]; some authors even proposed that all coronal jets originate from mini-filament eruptions, and their generation resembles the eruption of large-scale, energetic filament/CME eruptions [36,65,99].…”
Section: (B) Precursormentioning
confidence: 99%
“…Panesar et al [98] argued that the reason for flux emergence not directly causing jets is because the speed of emergence is seldom, if ever, fast enough. The emerging-reconnection scenario was challenged by the discovery of blowout jets that often involve the eruption of mini-filaments or filament channels [36,62,63,69,97] in association with flux cancellations [44,66,68,247,[304][305][306][307][308], and the cool component of blowout jets is actually the erupting filament material itself [44,63,69] rather than chromospheric material carried up by the emerging flux and accelerated by the show the direction of movement of the magnetic field lines, and features including the X-point, slow and fast shocks, and cool and hot jets are indicated [140].…”
Section: (A) Emerging-reconnection Modelmentioning
confidence: 99%
See 1 more Smart Citation